Measurement of Anti-Cyclic Citrullinated Peptide, Leptin Hormone, and Lipoprotein (a) In Iraqi Female Patients with Rheumatoid Arthritis - Abdul-Qahar, Zina H.; Mahmood, Halla G.; Rasheed, Manal k. (Journal of the Faculty of Medicine Baghdad, 2014)
Back ground:-Rheumatoid arthritis is one of the most common forms of inflammatory polyarthritis, with a prevalence of approximately 0.8% of adults worldwide, Rheumatoid arthritis patients may become disabled within few years if untreated that may lead to permanent disability. Different biomarkers have been assessed for the improved diagnosis of Rheumatoid arthritis, including a wide range of autoantibodies. However, only rheumatoid factor (RF) and anti-cyclic citrullinated peptide (ACCP) have gained wide acceptance. Aim of the study to investigate the levels of ACCP, Leptin, and Lipoprotein (a) in females with RA to provide information on possible pathophysiologic mechanisms, and to give recommendations for determination of these parameters in diagnosis and follow up of Rheumatoid arthritis patients. Patients and methods:- The study included Forty women with RA and Thirty apparently healthy women with matching age and weight as controls.The patients were selected at the outpatient clinic of Rheumatology & Rehabilitation in Medical City/ Baghdad Teaching Hospital during the period from (May2013 ) to (December2013 ). Results:-The results showed that levels of ACCP antibodies in serum of patients with RA were significantly higher than in serum of healthy control. Also there were significant differences between mean of serum leptin level and Lp (a) in patients compared to the control group. Conclusion:- Serum biomarkers like ACCP, Leptin, & Lipoprotein (a) assays are becoming increasingly available and may help in early diagnosis and assessment of complications in Rheumatoid arthritis patients.